“Onde estão nossas histórias?”: narrativas e memórias negras maracanauenses - Oliveira, Rebeca Silva de (2025)
This paper is an investigation into the stories, memories and identities of people of African descent who are members of the Racial Equality Council of Maracanaú, a municipality in the state of Ceará. Maracanaú is a young municipality, only 41 years old since its emancipation in 1983, with a population of 133,284 self-declared black and brown inhabitants, according to the IBGE in 2010. It is located in the metropolitan region of Fortaleza, 24 km from the capital, and is known for being the largest industrial center in the state. Part of its formation was the implementation of large housing estates which resulted in the migration of thousands of people from the countryside and also from Fortaleza, causing its population to increase more than fourfold in size in a decade. Using methodologies such as autobiography and Afro- descendant research, in which the researcher includes herself as part of the research, the work seeks to learn about the stories that are little shared in the imagination of Maracanaú, that is, those of black people. Through interviews, we understood the contributions of these narratives both to the construction of the city as it is seen today, and to the formation of an Afro-descendant identity within this territory based on collective and urban relations, since territory and memory define ethnic identity. Some of these stories were evoked from photographs in family albums, thus becoming past memories, told through present perspectives learned from new experiences. The research finds stories of a growing city, with a culture that is still inland, a strong sense of community and a connection with nature. In addition to black identities forged in popular and street culture, which suffer from the impact of racism, but which remain steadfast in the struggle to improve community life in the future through independent work. In conclusion, it is necessary to strengthen public policies based on the rights of the Afro-descendant community, so that the black identities of Maracanau are increasingly recognized and valued within the municipality.